3 - Contesting the African Public Sphere: A Philosophical Re-imaging of Power and Resistance in Ngugi’s Wizard of the Crow: https://doi.org/10.4314/ad.v34i2.57370 - Okolo, M. S. C. (Africa Development, 2009)
Habermas’s ideal notion of the ‘public sphere’ as the necessary condition for a genuine democracy is applied here in the assessment of the ideas contained in Ngugi’s Wizard of the Crow (2007) in an attempt to map out and understand the African public sphere. Wizard of the Crow employs the values of the public sphere to pass satirical comments on society’s values and practices: old assumptions are re-interrogated, established world-views reviewed and class and gender silenced issues revealed and re-evaluated. This paper adopts an interdisciplinary approach by employing philosophy and literature, here taken as Wizard of the Crow, as investigative tools. My choice of Wizard of the Crow to interrogate the African public sphere is particularly guided by the fact that to really encounter the public sphere is to first of all engage it at an imaginary realm. Besides, encountering the issues highlighted in Wizard of the Crow away from the structural discourse of the public sphere helps to humanize and plant them in the consciousness of people who may not have access to exotic academic presentation on the subject. Prefering a philosophical re-imaging of the concerns contained in Wizard of the Crow is to situate them within broader analytical frameworks. By adopting the basic methods of philosophical inquiry – exposition, critical analysis and reconstruction – the issues are lifted from the domain of fiction to the space of systematized knowledge directed at presenting a comprehensive notion of the African public sphere in as far as this can be achieved.